WAYANG KENTONGAN "BELL PUPPET" AS A MEAN OF COMMUNICATION IN EXPERIMENTAL THEATER - I Nyoman Sadi; I Nyoman Sedana; Ni Made Ruastiti; I Gusti Putu Sudarta (International Journal of Social Science, 2024)
He actual events of the life of the puppeteer artist with the traditional ritual life conditions of the Balinese people are the reality of life which can be seen as a human effort to optimize conditions that provide gaps in displaying desires/ego and idealized true existence. The situation of consciousness is realized through material reality that is rational and full of ethics and aesthetics in theater art. In the wayang kentongan work, a unique and interesting means of communication is realized in an experimental theater work. Puppet works Kentongan Puppet This is a new innovative wayang puppet made from bamboo in the shape of a kentonganas a means of communication with the community. Work show Experimental Theatre This harmoniously combines the movement of wayang, dance, accompaniment with the natural background of the village environment, the natural road with craftsmanship lighting modern. The work is studied descriptively and in-depth analysis using the social theory of kinship in community life that is able to live side by side, mutual cooperation, mutual care and nurturing. This performance in the form of puppet theater is expected to awaken human awareness of the importance of togetherness and mutual cooperation which has begun to fade due to human egoism. The communication interweaving of this experimental theater work can add to the form of presentation and treasure of Balinese skin puppetry, as a medium for delivering messages of education, philosophy, morals and ethics, kinship, cooperation, and cooperation